A two phased fuzzy methodology for selection among municipal projects - Baysal, Mehmet Emin; Kaya, İhsan and Kahraman, Cengiz and Sarucan, Ahmet and Engin, Orhan (Technological and Economic Development of Economy, 2015)
A municipality improves the quality of community life through its projects and actions. However, project selection and prioritization by municipalities are highly complex processes. Therefore, multicriteria decision making (MCDM) methodologies are very suitable for determining the best alternative. Recently, some studies have concentrated on the selection of the best project alternatives. In this paper, a two phased fuzzy MCDM methodology is proposed for the selection among municipal projects. In the first phase, fuzzy TOPSIS method is used to select the main project group and then fuzzy AHP is used to select the best sub-municipal project. The application of the suggested methodology has been made at the central district municipality in Konya, Turkey.